Prevalence and risk factors associated with stroke in middle-aged and older Chinese: A community-based cross-sectional study - Gan, Yong (Sci Rep, 2017)
Although the prevalence of stroke and its risk factors has been widely reported in some Western countries, information on essential stroke parameters is lacking in China, the most populous nation. A community-based cross-sectional study with 8,018 Chinese adults aged ≥40 years was used to determine the prevalence of stroke and associated risk factors. Within the screened population, the prevalence of stroke was 2.21% for both sexes, 1.60% for females, and 3.18% for males. Prevalence increased with age in both sexes (P < 0.0001). In a multivariable model, factors significantly associated with stroke were increasing age (odds ratio [OR] = 1.87, 95% CI: 1.58–2.24), male gender (OR = 2.03, 95% CI: 1.42–2.90), family history of stroke (OR = 4.33, 95% CI: 2.89–6.49), history of hyperlipidemia (OR = 1.87, 95% CI 1.31–2.68), history of hypertension (OR = 1.47, 95% CI 1.02–2.12), and physical inactivity (OR = 1.74, 95% CI: 1.16–2.59). The findings indicate that stroke prevalence in middle-aged and older Chinese adults is higher in males than in females, and increases with age in both sexes. Population-based public health intervention programs and policies targeting hyperlipidemia and hypertension control and encouragement of physical activity should be highly prioritized for middle-aged and older adults in Shenzhen, China.